2016
DOI: 10.11604/pamj.2016.23.108.8801
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome d’interruption de la tige pituitaire à révélation tardive

Abstract: Le syndrome d'interruption de la tige pituitaire est une cause assez fréquente de déficit en hormone de croissance et d'hypopituitarisme souvent révélé pendant la période néonatale et l'enfance. Cette observation illustre les particularités d'une révélation tardive de ce syndrome. Il s'agit d'une patiente âgée de 17ans hospitalisée pour aménorrhée primaire et impubérisme. Elle n'a pas d'antécédent d'incident néonatal. L'examen clinique révèle un retard de croissance sévère. L'hypophysiogramme a montré un hypop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The clinical consequences of pituitary hormone deficiency are diverse, including short stature, hypothyroidism, hypercortisolism, hypogonadism, and so on [5,12,13] . There are some late-onset reports of PSIS, [5,14] while PSIS manifested in newborns is rarely reported. However, the manifestations of neonatal PSIS are complex and serious, even life-threatening [3–6] .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical consequences of pituitary hormone deficiency are diverse, including short stature, hypothyroidism, hypercortisolism, hypogonadism, and so on [5,12,13] . There are some late-onset reports of PSIS, [5,14] while PSIS manifested in newborns is rarely reported. However, the manifestations of neonatal PSIS are complex and serious, even life-threatening [3–6] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these clear symptoms, very delayed diagnosis of panhypopituitarism has already been described, usually as single case reports (Table 3) [1,2,4,[6][7][8][9][10][11].…”
Section: Abstract Separated By ' -'mentioning
confidence: 99%
“…For example, Olszewska et al [ 3 ] published a case report of severe panhypopituitarism with PSIS in a newborn (4-day-old male) delivered by a mother with Turner Syndrome. Marmouch et al [ 4 ] reported a case of late PSIS onset in which a 17-year-old female patient presented primary amenorrhea and impuberism. Symptoms of PSIS can be overlooked during the neonatal period and infancy, therefore, diagnosis can be delayed.…”
Section: Introductionmentioning
confidence: 99%